Impact of carbon dioxide concentration on ASEAN capture fishery and aquaculture production - Goh, Jing Yu (2024)
Fisheries production refers to the number of aquatic species captured or cultivated for human use. It can be categorized into two types: capture fishery and aquaculture. The ASEAN region has significantly contributed to fisheries products, with the 10 ASEAN countries collectively accounting for a quarter of the world’s fish production. However, due to the rise in atmospheric carbon dioxide levels, extreme climate events have become more frequent compared to the past. These changes will severely impact fish populations and their habitats, ultimately disrupting the aquatic ecosystem. Hence, this research compares both production yields while considering the annual average global atmospheric carbon dioxide concentration. By referring to open-source data from National Oceanic and Atmospheric Administration (NOAA), World Bank, ASEAN Secretariat and International Monetary Fund (IMF), trend analysis can be performed to study impact of carbon dioxide concentration on ASEAN capture fishery and aquaculture production. Moreover, statistical model can be processed using IBM SPSS Statistics software with the data obtained, which is then utilized to predict the ASEAN capture fishery and aquaculture production.The results show the ASEAN capture fishery and aquaculture production models has an adjusted R squared value of above 0.9 which indicates a strong correlation with annual average global atmospheric carbon dioxide concentration. Furthermore, the standard error of estimate for ASEAN capture fishery exponential model is 0.055 tonnes while ASEAN aquaculture power model is 0.192 tonnes. Most importantly, each model has a p-Value less than 0.001 which means the models are statistically significant at confidence interval of 99%. The overall forecasting result of ASEAN capture fishery and aquaculture production shows an increase as the annual average global atmospheric carbon dioxide concentration increases with year. The upper bound predicted ASEAN capture fishery production yield is from logarithmic model with 19,798,511.18 tonnes, while the lower bound predicted production yield is from linear model with 18,082,735.22 tonnes. For ASEAN aquaculture production yield, the upper bound predicted is from power model with 51,061,322.27 tonnes, while the lower bound predicted production yield is from linear model with 30,204,252.63 tonnes.